2011
DOI: 10.1038/aja.2011.93
|View full text |Cite
|
Sign up to set email alerts
|

The X and Y chromosome in meiosis: how and why they keep silent

Abstract: T he XX/XY sex chromosomal system of mammals, including human, challenges the chromosome pairing mechanism during male meiosis. Pairing and subsequent separation of homologous chromosomes generates haploid cells from diploid cells during the meiotic divisions. One of the basic requirements for recognition between homologous chromosomes is DNA sequence identity. Since the X and Y chromosome share little homology, their quest for each other is difficult, and has special characteristics. During the lengthy meioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…During meiosis in eutherians and marsupials, the X and Y chromosomes undergo meiotic sex chromosome inactivation (MSCI), in which most sex-linked genes are inactivated [104][105][106][107][108]. This process is mediated by epigenetic modifications, through chromatin condensation and heterochromatin formation, and the X and Y chromosomes are packaged into a compact structure, called the sex body [104][105][106][107][108]. MSCI is initiated at meiotic prophase I and is retained during late spermatogenesis, repressing most sex-linked genes during sperm differentiation.…”
Section: Meiotic Sex Chromosome Inactivationmentioning
confidence: 99%
“…During meiosis in eutherians and marsupials, the X and Y chromosomes undergo meiotic sex chromosome inactivation (MSCI), in which most sex-linked genes are inactivated [104][105][106][107][108]. This process is mediated by epigenetic modifications, through chromatin condensation and heterochromatin formation, and the X and Y chromosomes are packaged into a compact structure, called the sex body [104][105][106][107][108]. MSCI is initiated at meiotic prophase I and is retained during late spermatogenesis, repressing most sex-linked genes during sperm differentiation.…”
Section: Meiotic Sex Chromosome Inactivationmentioning
confidence: 99%
“…The authors also confirmed that the transcription of some spermiogenesis-related genes is initiated as early as pachytene Spc. They also found that some Xlinked genes are overexpressed during meiosis, thus escaping the meiotic sex chromosome inactivation (MSCI) (Ichijima et al, 2012;van der Heijden et al, 2011). Another RNA-seq study on five enriched mouse GCs populations focused on lncRNAs and also identified candidate genes that escape MSCI (Wichman et al, 2017).…”
Section: Gene Expression Program At Play During Spermatogenesismentioning
confidence: 99%
“…1). Unlike autosomes that undergo synapsis along their entire lengths during meiosis, large regions of the X and Y chromosomes remain unsynapsed and trigger transcriptional silencing, called meiotic sex chromosome inactivation (MSCI: reviewed elsewhere (Ichijima, et al 2012, Turner 2007, van der Heijden, et al 2011)). MSCI is accompanied by the formation of distinct heterochromatin called the XY body (also known as the sex body).…”
Section: Introductionmentioning
confidence: 99%